(untitled) (KULT_online, 2020)
Kulturelle Übersetzer (eng.: Cultural Translators) is an edited volume published by transcript Verlag and edited by Christiane Dätsch. The contributions examine the concept of practice-based cultural translation, specifically within the German transcultural context of the arts and of arts management, and contribute to the larger discourse about transculturality within the arts. Both those working within the cultural sector as well as practice-oriented cultural studies scholars can benefit from the variety of cases and disciplines presented within the book.